2014
DOI: 10.5830/cvja-2014-010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prehypertension on left ventricular mass and QT dispersion in adult black Nigerians : cardiovascular topic

Abstract: SummaryBackgroundPrehypertension has been associated with target-organ damage. This study sought to determine the impact of prehypertension (PHT) on QT dispersion and left ventricular hypertrophy (LVH) in adult black Nigerians.MethodsOne hundred and one subjects with office blood pressure (BP) < 140/90 mmHg were categorised according to their office BP into normotensive (BP < 120/80 mmHg, n = 57) and prehypertensive (BP 120–139/80–89 mmHg, n = 44) groups. Echocardiography and electrocardiography (ECG) were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
1
3
1
Order By: Relevance
“…normotensives [18], although their study participants had far higher LVMI than the participants in the study by Doğru et al [10] and the participants of our study.…”
Section: Discussioncontrasting
confidence: 75%
“…normotensives [18], although their study participants had far higher LVMI than the participants in the study by Doğru et al [10] and the participants of our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Our study showed that the LVMI was significantly higher in prehypertensive subjects than in normotensive subjects. This correlates with the work of Ale et al [10] in Nigeria and other studies [21,22], including the Strong Heart Study [7]. The findings of a significantly higher left ventricular internal diameter in diastole (LVIDd), left ventricular posterior wall in diastole (LVPWd), and relative wall thickness (RWT) in prehypertensive individuals in the current study corroborate the ARIC (Atherosclerosis Risk in Communities) study [23] where LVIDd and LVPWd were significantly higher in prehypertensive subjects compared to normotensive controls amongst Americans.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, no study has examined LV geometry and function in young Nigerians with prehypertension. The few studies conducted on LV geometry in Nigeria mostly studied hypertensive subjects, and the results from these studies were correlated to international studies; abnormal LVMI with a predominant pattern of concentric left ventricular hypertrophy (LVH) [ 10 , 11 ]. In addition, the participants in these studies were middle-aged, with a sparse representation of young patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nwatu et al [27] have shown that impaired glucose tolerance were significant predictors of prehypertension. Ale et al [34] measured the impact of prehypertension on some electrocardiographics and echographic factors. They noticed that compared with normotension, prehypertension was associated with higher left ventricular mass and higher left ventricular mass index.…”
Section: -Cardiometabolic Factorsmentioning
confidence: 99%